Auger electron spectroscopic analysis of corrosion products formed on A3003 aluminum alloy in model fresh water with different Zn2+ concentration. (4th February 2019) - Otani, Kyohei; Islam, Md. Saiful; Sakairi, Masatoshi; Kaneko, Akira
Abstract : The corrosion morphology and composition of corrosion products of A3003 formed in model fresh water with different Zn 2+ concentrations were investigated by immersion tests combined with surface observations and analysis using an Auger electron spectroscope (AES). The cross‐sectional AES observations showed that the thickness of the corrosion product layer formed on A3003 decreases with increases in the Zn 2+ concentration of the model fresh water. A cross‐sectional AES point analysis suggested that the corrosion products formed on the A3003 in the Zn 2+ containing model fresh water (Zn 2+ > 0.1 mM) have a multilayered structure and that the inner of Zn‐rich layer would have high corrosion protective properties.